Syntheses of new butylated hydroxytoluene analogues and their potential application as antioxidant for synthetic lubricant oil / Amit Ranjan Nath - Amit Ranjan , Nath (2019)
Antioxidants are familiarly involved in the prevention of cellular damages as well as oxidative damages of chemical products caused by free radicals. Therefore, discovering the efficient multifunctional antioxidants is the continuous research to prevent the oxidation related problems effectively such as oxidative stress and pre-mature oxidation. In search of new multifunctional or multipotent antioxidants, four multifunctional antioxidant structures were prepared by assembling multiple antioxidant functions in a single structure. In this study, N1-(3,5-di-tert-butyl-4-hydroxybenzylidene)-N4-(substituted phenyl)-semicarbazone (5.7a-5.7j) and N1-(3,5-di-tert-butyl-2-hydroxybenzylidene)-N4-(substituted phenyl)-semicarbazone (5.10a-5.10j) were two envisioned multifunctional antioxidant structures, butylated hydroxyphenyl (BHP) incorporated semicarbazones, which were prepared from thiolated substituted semicarbazides bearing butylated hydroxyphenyl (5.5a-j) upon heating in the acidic ethanol in the presence of 3,5-di-tert-butyl-4-hydroxybenzaldehyde and 3,5-di-tert-butyl-2-hydroxybenzaldehyde respectively. The compounds 5.5a-j were also the designated multifunctional antioxidant structure which is the combination of multiple antioxidant functions such as BHA, thioether and aromatic secondary amine. Series 1 (5.7a-5.7j) and series 2 (5.10a-5.10j) were carried out DPPH assay to investigate the antioxidants properties. Series 1 compounds (5.7a-5.7j) were found as an efficient free radical scavenger in DPPH assay in comparison with standard BHT and Series 2 compounds. The increasing order of IC50 were found for Series 1 as follow as 5.7a >5.7b >5.7h >5.7e >5.7c >5.7g >5.7d >5.7i > BHT >5.7j >5.7f. Incorporation of 3,5-di-tert-butyl-4-hydroxyphenyl to semicarbazones (compounds 5.7a-e, 5.7g-i) increased the antioxidant activity notably. It was concluded that hydrogen bond in Series 2 structure might be responsible for the lower antioxidant properties. Based on the solubility in synthetic lubricant oil trimethylolpropane trioleate (TMPTO) and obtained DPPH results, synthesized compounds were carried out several oxidation tests to evaluate the oxidation stability. The compounds (3,5-di-tert-butyl-4-hydroxy-benzylsulfanyl)-acetic acid methyl ester (6.1) showed promising oxidative stability to TMPTO oil in DSC, RBOT and thermogravimetric analysis in comparison with commercial antioxidants BHT and Irganox 1076. To obtain those above-designated compounds, a new reaction protocol for the preparation of semicarbazones became necessary to develop due to all the contemporary methods suffer from several limitations. Therefore, in this study, an efficient and robust reaction protocol was developed which provides a variety of antioxidant structures based on BHT moiety including the designated structures and also able to overcome the existing limitations. A variety of semicarbazones (28 compounds 4.7a-4.7g, 4.7a1-4.7g1, 4.7a2-4.7g2, 4.7a3-4.7g3) were initially prepared to validate the reaction protocol as proof of versatility, functional group compatibility and higher product yields of this method. This reaction can also help to get distinct substitution derivatives of semicarbazides forming a more carbon-nitrogen bond which will allow further research.